Gloria [videorecording (DVD)] - Lelio, Sebastián, 1974-; Lelio, Sebastián, 1974-; Hernández, Sergio; García, Paulina
A story about a middle aged woman who gets caught up in a passionate whirlwind romance with a retired naval officer, whom she meets at a dance club for singles. But when she discovers the truth of their relationship, she takes matters into her own hands and sets forth to change her life.